STRUCTURAL AND DESIGN MODIFICATION OF A 1-TON CAPACITY MOVABLE LIFTING SYSTEM WITH ELECTRIC MOTOR DRIVE - YANEL, KARNOVA; Saferi, Rozi; Eka Putra, Ismet (Jurnal Teknologi dan Vokasi, 2026)
This study investigates the structural and design modification of a 1-ton capacity movable goods lift that was originally operated using a manual hand winch system. The conventional system exhibited several limitations, including high operator effort, insufficient safety features, and inadequate structural stability, which increased the risk of occupational accidents. To overcome these limitations, the lift system was modified by integrating a DC electric motor as the primary drive unit, reinforcing the frame structure with foldable support legs to enhance stability, and incorporating an emergency braking mechanism (spring knife) to improve operational safety. The research methodology included mechanical design, structural analysis, and static load simulation using engineering simulation software. The simulation results indicate that the modified structure provides more uniform load distribution, reduced deformation, and Von Mises stress values that remain within the allowable limits of the material. These findings demonstrate that the proposed modification significantly improves efficiency, safety, and ease of operation. Therefore, the modified movable lift is suitable for practical implementation in workshops, warehouses, and laboratory environments.